1992
DOI: 10.1037/0278-7393.18.6.1284
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect measures of memory for modality in young and older adults.

Abstract: In 2 experiments, young and older adults demonstrated modality effects of similar magnitude in perceptual identification tasks. That is, both young and older adults demonstrated more repetition priming when study and test modalities matched than when they were different, suggesting that contextual information was equally available across age. However, when asked explicitly to retrieve modality information, older adults were less accurate than young adults. These results constitute evidence for a dissociation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
104
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 59 publications
(78 reference statements)
14
104
1
1
Order By: Relevance
“…However, older adults did not show a more robust eye movement effect for the relations among the objects when compared with the younger adults; in fact, only the younger adults showed eye movement evidence of memory for the relations. Because our results were obtained using an implicit eye movement task, consistent findings of an age-related binding impairment obtained with explicit memory instructions, as in studies of associative memory (Chalfonte & Johnson, 1996;Light & La Voie, 1993;Light & Singh, 1987;Naveh-Benjamin, 2000;Winocur et al, 1996), are unlikely to be solely attributable to the increased anxiety and arousal caused by explicit memory instructions (cf. Rahhal et al, 2001).…”
Section: Age-related Impairments In Bindingsupporting
confidence: 86%
“…However, older adults did not show a more robust eye movement effect for the relations among the objects when compared with the younger adults; in fact, only the younger adults showed eye movement evidence of memory for the relations. Because our results were obtained using an implicit eye movement task, consistent findings of an age-related binding impairment obtained with explicit memory instructions, as in studies of associative memory (Chalfonte & Johnson, 1996;Light & La Voie, 1993;Light & Singh, 1987;Naveh-Benjamin, 2000;Winocur et al, 1996), are unlikely to be solely attributable to the increased anxiety and arousal caused by explicit memory instructions (cf. Rahhal et al, 2001).…”
Section: Age-related Impairments In Bindingsupporting
confidence: 86%
“…An ironic effect of repetition, as denned here, reflects a failure to recollect that a word was read, rather than heard, earlier. Results from standard tests of source memory have shown that older, as compared with younger, adults are less able to remember whether information was presented visually or aurally (e.g., Light, La Voie, Valencia-Laver, Albertson-Owens, & Mead, 1992;Mclntyre & Craik, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Camp et al (2000) have argued that SR better taps a more implicit/automatic memory system than other mnemonic techniques. Compared with tasks that tap conscious recollection, implicit memory tasks (e.g., as reflected by repetition priming effects) appear to be relatively intact in both healthy older adults and individuals with early stage DAT (see, e.g., Balota & Ferraro, 1996;Ferraro, Balota, & Conner, 1993;Gabrieli et al, 1999;Light & LaVoie, 1993). In this light, it is interesting to note that Spieler and Balota (1996) and Faust et al (2001) have found that both healthy older adults and individuals with early stage DAT produce the same benefits of spacing and repetition in learning unrelated pairs of words in speeded naming performance.…”
Section: Why Might Expanded Retrieval Practice Produce Amentioning
confidence: 99%